Faculty Attitudes Toward Athletics at NCAA Division II Institutions - Travis Feezell (Journal of Applied Sports Management, 2013)
Faculty members at institutions in three Division II conferences were surveyed regarding their opinions on general issues in intercollegiate athletics. In addition, faculty members at these institutions were asked to express their opinions and understanding as to the role of intercollegiate athletics and the place of faculty governance of athletics at their respective institutions. Analysis revealed that the demographic characteristics of NCAA divisional status, institutional status, gender, and past participation in athletics do influence the attitudes of faculty members and that these attitudes generally differ from faculty colleagues in Divisions I and III. Moreover, analysis noted that Division II faculty members see little faculty engagement with athletics and thus see little faculty governance beyond that of the appointed Faculty Athletics Representative. Finally, Division II faculty members noted a utilitarian function for athletics, often being utilized as a recruitment tool for students or providing activity for some segment of a varied student population.
Keywords: Faculty; intercollegiate athletics; faculty governance; FAR